Dr. Seuss The cat in the hat - Kalter, Alan.; Seuss, Dr.; Green Light Media; Random House Video; Random House (Firm); Sony Music Entertainment, Inc.; Sony Wonder (Firm) (New York, NY : Random House ; New York, NY : Distriubted by Sony Music Entertainment and Sony Wonder, 2002)
The cat in the hat: Dr. Seuss's cherished mischievous cat who brightens a brother and siter's boring rainy day. Encourages young viewers to seak out the book and bring it to life in their own imagination. Maybe you should fly a jet! Maybe you should be a vet!: For kids of all ages who are wondering what to be when they grow up. This delightful story offers some wonderfully wacky suggestions.
The cat in the hat -- Maybe you should fly a jet! Maybe you should be a vet!
Originally aired in 1997.
Based on the books created by Dr. Seuss.
Voice: Alan Kalter.
MPAA rating: Not rated.
DVD, Region 1, full screen presentation; Dolby Digital.
Closed-captioned.
Keywords: Cat in the Hat (Fictitious character) -- Juvenile drama; Imagination in children -- Juvenile drama; Occupations -- Juvenile drama; Short films; Animated films; Children's films; Video recordings for the hearing impaired; DVD-Video discs; DVDs